High water content hydrogel with super high refractive index - Zhou, Chuncai (2014)
Transparent, high water content (>65%), and cytocompatible hydrogels, which also possess super high refractive indices (RI > 1.5), are needed for ophthalmological applications. Most hydrogels can achieve either high RI or high water content but not both in the same system because water is a low RI material. Here, high water content/high RI hydrogels fabricated through elevated-temperature UV polymerization of an aqueous solution of acrylamide (AM) and methacrylamide (MAM) with tri(ethylene glycol) dimethacrylate (TEDA) crosslinker are reported. By varying the AM:MAM ratios (2:8 to 8:2) and crosslinker density (5 to 11 mol %), it is discovered that high water content (66%) AM:MAM copolymer hydrogels exhibiting anomalously high refractive indices (1.53); they are also colorless, transparent (99.4%), and cytocompatible with human keratinocytes.